Community health agents as facilitators in the suspicion of leprosy in risk areas identified through spatial analysis - Carvalho, Marcos Mickael Gomes; Souza, Catarina Isabor Gomes; Gomes, Glauciney Pereira; Baia , Marcos José da Silva; Gomes , Vilmar Pereira; Conde, Guilherme Augusto Barros (Seven Editora, 2023)
Objective: to evaluate community health agents in the identification of individuals suspected of leprosy in their coverage areas through spatial analysis. Methods: a cross-sectional, descriptive, and quantitative study. We used the cases reported in the Information System of Notifiable Diseases, 2006-2014. We included 24 agents from basic health units located in areas of a low, medium, and high degree of leprosy detection. Results: 83% of the agents recognized leprosy as an infectious-contagious disease. However, in the transmission and surveillance of contact, only 50% demonstrated to know. During the home visit, 19 suspected cases had spots on the skin, 13 with neurological changes such as pain, numbness, and tingling. Conclusion: limited knowledge can hinder the approach of the agent with the individual with suspicion of the disease, reflecting in actions for the control of leprosy, since this agent greatly amplifies the capillarity of the health system in the active search for new cases of the disease. DOI:https://doi.org/10.56238/alookdevelopv1-091